Cyclic Vomiting Syndrome in Adults and Children: A Hypothesis. Issue 6 (10th May 2017) - Redon, Sylvain; Mareau, Cécile; Guedj, Eric; Donnet, Anne
Abstract : Objective: To see how patients' clinical descriptions compare to the third classification of International Classification of Headache Disorders (ICHD‐III beta). Background: CVS is an episodic syndrome associated with migraine. It is a rare disorder of childhood and adulthood. New criteria are proposed in the third classification of International Classification of Headache Disorders. Methods: This study describes children and adults' CVS characteristics at a French tertiary‐care center, according to the ICHD‐II and ICHD‐III beta criteria. Clinical features, and results of paraclinical tests were characterized. Results: Fifteen patients were included: 8 adults, 2 children, and 5 adolescents. Familial history of migraine or CVS was respectively noticed in 12 and 4 patients. The duration of premonitory, emetic, and postdromal phases was evaluated from hours to days. Some symptoms described in theses phases are also described in migrainous population, with a comparable frequency. Cranial or systemic autonomic symptoms were respectively reported in 47% and 93%. Nine patients described a circadian periodicity, and six patients described a circannual periodicity. The predictable periodicity was from 1 week to 12 months. A brain perfusion SPECT showed an increased hypothalamic perfusion during emetic phase in one patient. Conclusions: CVS is a rare episodic syndrome associated with migraine. Some clinical features and paraclincal tests suggest a chronobiological disease.